Values, optimum stimulation levels and brand loyalty: New scales in new populations - Steven M. Burgess; Mari Harris (South African Journal of Business Management, 1998)
The optimum stimulation level (OSL) and value priorities of 3 493 South Africans were measured in the first administration of Steenkamp and Baumgartner's new shortened Change Seeker Index (CSl) and Schwartz' new Portraits Questionnaire (PQ) in a nationally-representative developing nation sample. Both instruments performed well in a demanding cross-cultural test as part of a syndicated research study. The results indicate that high and low OSL consumers exhibit value differences consistent with Schwartz' theory about the content and structure of values suggesting that the shortened CSI may be tapping value differences. The predicted sinusoid pattern between value priorities and OSL also emerged. The association between values and brand loyalty exhibited three general sinusoid patterns. Comparative sample partitions based on value priorities and OSLs suggest that values may be sensitive to a wider range of motivations that underlie differences in exploratory product acquisition, shopping behaviour and brand loyalty. The results suggest that value priorities and OSL are important influences on brand loyalty behaviour.
Keywords: 650